Islam Moderat antara Konsep dan Praksis di Indonesia - Sartika, Dani (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2020)
The Islamic moderation is the efforts to tend the tradition and making the equalled idea of gracious Islam. The purpose of this research is to delve the moderate Islam which becomes the deals between the right extreme group and the left extreme group. This is the solution from many horizontal conflicts which is caused by the different perception of religion nowadays. The method that used by the researcher in this study is the scientific method analysis. This analysis is the way which is using many procedures to analysing and making the valid conclusion from the document. In this implementation, the writer researches many literatures, manuscript, particularly the education journals to study which is related to this research. The result from the research finds that popularizing Islam moderate in Indonesia is the obligation. The concern Islam is not only about worship, but also caring to all Muslims, moreover for all the human being with the different background own. Regarding and caring the natural sustainability is the Islamic teaching of hablum minal alam obligaton. Created as rahmatan lil ‘alamanin thought, that is one of the Islam moderate reference, returning the real of Islam which is known as the religion of full of grace and affection. The Islam moderate or also called wasatiyyah al-islam is Islam which always indicated by harmony, impartiality, wisdom, tolerance, acceptance, respect, inclusive, non-violence, non-extremism, non-radicalism and non-terrorism. The existence of living safe, peacefulness, and welfare in this world is according to Islam. That is one of the biggest religion in the world. With the thought which is prioritizing social approach, nationality, culture and humanity